Digital Transformation in Archival Management: A Case Study of the PQX Study Program - Elviana, Rahmi; Delfebriyadi, Delfebriyadi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The PQX Study Program is part of a State University in Indonesia, faces significant challenges in managing academic and administrative archives. Based on internal data until October, 2025, more than 6000 physical records are still managed manually or stored through online media such as Google Drive, without an integrated archiving system or adequate security mechanisms. This condition has resulted in delays in data retrieval, limited storage capacity, and increased operational costs due to the maintenance of physical archives. To address these issues, this study applies a software engineering approach using the System Development Life Cycle (SDLC) model to design a web-based archival information system prototype. The purpose of this research is to develop an integrated archival information system within the PQX Study Program. The research stages include user needs analysis, system design using a user-centered design approach, and prototype implementation. Data were collected through observation, and analysis of internal archival documents. The resulting digital archiving system design is expected to enhance document access efficiency, strengthen data security, and support the digital transformation of academic administration within the PQX Study Program.